Voice transmission over PC network - Abdul Rashid, Zainal Abidin; Ismail, Mahamod; Mohd Ali, Borhanuddin (1990)
With the merger of telecommunication and computer technologies, voice transmission over computer networks has now become possible. This paper describes two types of voice communication over PC networks; a single point-to-point link, using store and forward concept (delayed message technique) for developing voice mail system, and a voice/data integration over Ethernet Local Area Network (LAN). Voice signal sampled from telephone handset is digitized and coded to 4-bit ADPCM codeword by the codec which is interfaced to the PC. In the voice mail example, the digitized data is stored in the PC and subsequently transmitted over a simple point-to-point link to a remote PC. In the second example, the voice data is immediately transmitted via a buffer to the destination station, using Carrier Sense Multiple Access with Collision Detection (CSMA/CD) medium access protocol. A corresponding codec at the receiver end will decode the digitized voice and convert back to analog signal before being played out on the telephone earpiece.